Elites científicas junto às políticas locais de C&T: o caso da Secretaria Municipal de São Carlos-SP - Thales Haddad Novaes de Andrade; Karina de Camargo (Ciências Sociais Unisinos)
This article deals with the presence of scientific and technological elites in the implementation of local Science and Technology (S & T) policies in Brazil. In the last decades there has been an increasing growth of municipalities formulating their own policies in the field of science and technology, in order to articulate scientific knowledge and local development programs. The main issue proposed in this article is to discuss the presence of local scientific elites in the definition of S & T policies at the municipal level and how they articulate with decision makers. A case of study was carried out in the city of São Carlos (SP), a high-tech center linked to research and higher education institutions. At the end of the 1990s a Municipal Department was created in the city, which was used as a basis for our analysis. It was verified that these scientific elites act consistently in their own academic domains, but are subordinate in the process of institutionalization of S&T area at the local level.